The Effect Of Perceived Usefulness, Perceived Ease Of Use And Perceived Trust On The Interest Of Muhammadiyah Sidoarjo University Student In Using Electronic Money: Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan dan Persepsi Kepercayaan terhadap Minat Mahasiswa Universitas Muhammadiyah Sidoarjo dalam Menggunakan Uang Elektronik - Nafiatur Rohmah; Futri Nur Latifah (Universitas Muhammadiyah Sidoarjo, 2021)
The effect of perceived usefulness, perceived ease of use and perceived trust on the interest of Muhammadiyah SidoarjoUniversity student in using electronic money. This studywas used to determine whether perceived usefulness, perceived ease of use and perceived trust had an effect on student interest at Muhammadiyah University of Sidoarjo in using electronic money. The research method used is quantitative using 102 respondents with proportionate stratified random sampling technique. The results of this study indicate that partially perceived usefulness have 3,225 > 1,985 with a significance of 0,002 < 0,05, perceived ease of use has 0,720 < 1,985 with a significance of 0,473 > 0,05, perceived trust has 4,254 > 1,985 with a significance of 0,000 < 0,05, meanwhile simultaneously perceived usefulness, perceived ease of use and perceived trust have 22,618 > with a significance 0,000 < 0,05. From the results of the study, it can be concluded that partially the perceived usefulness and perceived of trust affect the interest of Muhammadiyah Sidoarjo University students in using electronic money, while the perceived ease of use does not affect the interest of Muhammadiyah Sidoarjo University students in using electronic money. Simultaneously the perception of benefits, the perception of ease of use and the perception of trust affect the interest of Muhammadiyah Sidoarjo University students in using electronic money